Cell biology of ageing. IV. Effect of Nordihydro-guaiaretic acid (NDGA) and cortisone on the ageing syndromes of early senescent mutants of N. crassa. - M. S. Islam; A. Nessa (Fungal Genetics Reports, 1987)
Cell biology of ageing. IV. Effect of Nordihydro-guaiaretic acid (NDGA) and cortisone on the ageing syndromes of early senescent mutants of N. crassa.